ASSESSMENT OF THE PROTECTIVE ROLE OF MYOCARDIAL BRIDGING AGAINST ATHEROSCLEROSIS IN THE CORONARY SYSTEM - KHAWAJA , MSF; SAEED , HY; BASHIR , M; HASHMI , KA (Biological and Clinical Sciences Research Journal, 2023)
The retrospective study was based on data collected from tertiary care hospitals from May 2022 to November 2022 to evaluate the association between myocardial bridge and obstructive atherosclerosis, which requires treatment with coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI), in coronary system. Patients diagnosed with or likely to have coronary artery disease, coronary angiography of whom was performed, were included in the study. Of 1000 patients who underwent angiography, 80 (50 males and 30 females) had MB located in the left anterior descending artery (n=72), left circumflex (4), and right coronary artery(4). The occurrence of myocardial bridging in the SOCAD and SOCAD groups was significantly different and significantly lower in SOCAD compared to non-SOCAD groups (P< .0001). There was a significant negative linear correlation between MB and SOCAD (P <.0001). Log OR of MB was -2.135, suggesting the protecting effect of MB against SOCAD. It is concluded that myocardial bridging protects against atherosclerosis in the coronary system.